SHARED READING MENGGUNAKAN BIG BOOK TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA TUNARUNGU KELAS 1 SDLB-B - salma nurliana, dahniar (Jurnal Pendidikan Khusus, 2016)
Abstract Hearing impairment had impact to the impeded children’s language development. It caused complex development problem, such as the low entering information, disturbed social interaction, hampered intelligence ability, and emotion. Therefore, the development of language skill had to be implemented as early as possible. One of them developed reading skill through Shared Reading. The purpose was to describe whether there was the influence of shared reading using big book toward beginning reading ability to the first class of hearing impairment students in SDLB-B Kemala Bhayangkari I Trenggalek or not. This research approach was quantitative with pre-experiment kind, and one group pretest-posttest design. The independent variable of shared reading used big book and the dependent variable was beginning reading ability. The research subject was the first class of hearing impairment students in SDLB-B Kemala Bhayangkari I Trenggalek numbering 8 children. The data collection used oral test (reading), the data analysis used was sign test. The result of data analysis indicated that the average value of beginning reading ability pre test was 56,53 and the post test was 83,02. Z table 5% to two sides test was 1,96 and the Zh value obtained was 2,48. Based on the result of data analysis it could be concluded that there was significant influence of using Shared Reading with Big Book toward beginning reading ability to the first class of hearing impairment students in SDLB-B Kemala Bhayangkari I Trenggalek.     Keywords: Shared Reading, Big Book, beginning reading